2006
DOI: 10.1016/j.juro.2006.07.146
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Postoperative Renal Function in Patients Undergoing Ileal Conduit Diversion for Cancer Measured Using Serial Isotopic Glomerular Filtration Rate and 99m Technetium-Mercaptoacetyltriglycine Renography

Abstract: Of patients with an ileal conduit 29% have renal function deterioration in the long term. No surgical cause for glomerular filtration rate deterioration was found in 18%. Important predisposing factors in nonobstructed cases were hypertension, recurrent urinary sepsis and a glomerular filtration rate of less than 50 ml per minute per 1.73 m. Hypertension was an independent predictor of a decreased glomerular filtration rate in the group with worsening glomerular filtration rates. In 11% of patients deteriorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 17 publications
1
18
0
5
Order By: Relevance
“…6 Samuel et al evaluated renal function after IC using 99m technetium-mercaptoacetyltriglycine renography and noted that 29% of patients had evidence of renal function deterioration with worsening GFR. 16 Jin et al evaluated a cohort of patients with IC and CD, and found that approximately 25% had a GFR decrease of greater than 10 ml/minute/1.73 m 2 at 10-year followup. 17 Additional single institution studies identified rates of renal deterioration as high as 70% 10 years after cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Samuel et al evaluated renal function after IC using 99m technetium-mercaptoacetyltriglycine renography and noted that 29% of patients had evidence of renal function deterioration with worsening GFR. 16 Jin et al evaluated a cohort of patients with IC and CD, and found that approximately 25% had a GFR decrease of greater than 10 ml/minute/1.73 m 2 at 10-year followup. 17 Additional single institution studies identified rates of renal deterioration as high as 70% 10 years after cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This result is comparable to the previous study in which there was 18-29% of patients revealed worsening of renal function during a median follow-up of 8 years. 6 Chemotherapy after radical cystectomy was found to be a significant determinant of postoperative renal function. M-VAC is the standard regimen which was used.…”
Section: Discussionmentioning
confidence: 99%
“…5 Samuel et al showed that 18% of sources were non-surgical. 6 Studies have shown that risk factors such as age, gender, hypertension, diabetes, preoperative ABSTRACT Background: Ileal conduit (IC) is the most commonly performed urinary diversions (UD) contributing 33-72 % of all types of UD with. Ileal conduits are relatively easy and quick to create, with a low rate of surgical complications.…”
mentioning
confidence: 99%
“…Renal function impairment in patients with bowel interposition in the urinary tract is generally attributed to obstructive causes with or without recurrent infection or hypertension [7]. Early detection of renal function deterioration and identification of causative factors are crucial in preserving renal function in this group of patients.…”
Section: Discussionmentioning
confidence: 99%